Gender balance and its impact on male and female smoking rates in Chinese cities. (April 2016) - Yang, Tingzhong; Barnett, Ross; Jiang, Shuhan; Yu, Lingwei; Xian, Hong; Ying, Jun; Zheng, Weijun
Abstract: Objective: Although gender differences in smoking have received much attention, few studies have explored the importance of contextual effects on male and female smoking rates. The aim of this study is to examine the association between variations in city-level sex ratios and gender differences in smoking in China. Methods: Participants included 16, 866 urban residents, who were identified through multi-stage sampling conducted in 21 Chinese cities. Results: The study found that, independent of personal characteristics, cities with more males had higher male smoking rates and lower female rates. Conclusions: Our research underscores the importance of city-level contextual effects in understanding gender differences in smoking in China. Highlights: City-level sex ratios have an independent effect on male and female smoking prevalence. We highlight different pathways by which urban sex ratios may influence smoking. Male cultural norms are the most likely cause of gender differences in smoking in China. Tobacco control policies in China need to be aware of changing gender roles.